The role of skeletal muscle in the initiation and progression of knee osteoarthritis - Tonge, Daniel Paul (2010)
It is established that patients with knee osteoarthritis (OA) exhibit marked muscle weakness, one of the most frequent and earliest reported symptoms associated with knee OA. Weakness primarily affects the quadriceps muscle with little evidence of hamstring involvement. Traditionally, muscle weakness has been considered a secondary effect in knee OA, resulting from disuse of the affected joint due to the presence of pain and/or inflammation, and therefore has received little attention with regards to its involvement in the initiation or progression of OA. However, there is clinical evidence which suggests that quadriceps weakness may precede the onset of radiographic evidence of OA and subsequent pain, and therefore may be directly involved in its pathogenesis. Furthermore, targeted exercise regimes aimed at improving quadriceps function indicate therapeutic benefits with regards to both the initiation and progression of knee OA. Quadriceps muscle dysfunction in knee OA is currently poorly understood and represents an unmet clinical need.